A SOCIAL RETURN ON INVESTMENT ANALYSIS ON COMMUNITY BASED DISASTER MANAGEMENT TO RESPOND TO PANDEMIC COVID - Harahap, Reiki Nauli; Harlyandra, Yorry; Dinariratri, Anna Svetla; Putri, Mozara Kartika (Universitas Negeri Yogyakarta, 2023)
The Covid 19 pandemic has hit various aspects of life in society. Disaster management programs carried out by the government are not fully effective, and community-based disaster management is one solution for this case. One of the problems faced by community-based disaster management is the lack of funding support. Business sector involvement is needed to strengthen community-based disaster management. Inviting multi-stakeholders by involving the community, the business, and the government to provide real solutions to the limitations of disaster programs. This research uses a qualitative and quantitative mixed method with a social return on investment calculation approach to facilitate the process of analyzing the success of community-based disaster management programs. The results of the study stated that the